48th Winter School on Wave and Quantum Acoustics XLVIIth Winter School on Environmental Acoustics and Vibroacoustics Szczyrk, Poland, 25.02–01.03.2019 - Schools on Acoustics, Winter (Archives of Acoustics, 2019)
48th Winter School on Wave and Quantum Acoustics constituted platforms for sharing the results and achievements obtained in different branches of physical acoustics (e.g. molecular acoustics, quantum acoustics, acousto-optics, magnetoacoustics, photoacoustics, acoustics of solid state, acoustic emission etc.). Moreover, researches in some selected topics related to those mentioned above (e.g. optoelectronics, relaxation processes) were presented during the school. Conference consisted of 15th Workshop on Acoustoelectronics and 15th Workshop on Molecular Acoustics, Relaxation and Calorimetric Methods. However, there is a possibility of organizing workshops on other subjects in the future. We would like to invite scientific centers and groups to cooperate in organizing workshops on the subjects of their interests. XLVIIth Winter School on Environmental Acoustics and Vibroacoustics was the forum for all environmental and vibroacoustics fields. Particularly it concerned traffic noise, vibroacoustics of machines, room acoustics, building acoustics, noise protection and similar problems.